2019
DOI: 10.3389/fnins.2019.00866
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-126-3p Attenuates Intracerebral Hemorrhage-Induced Blood-Brain Barrier Disruption by Regulating VCAM-1 Expression

Abstract: Background miR-126 is closely related to the occurrence of various complications after intracerebral hemorrhage (ICH), but the molecular mechanism is not fully elucidated. This study aimed to explore the mechanism of miR-126-3p in alleviating brain injury after ICH. Methods Serum miR-126-3p levels were compared between patients with IHC and healthy controls. A rat model of ICH was generated by intracerebral injection of Type VII collagenase. The rats were intracerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…miR-126 also regulates BBB or BRB function. miR-126-3p mimic or miR-126 expressing plasmid attenuated hemorrhage-induced BBB or ischemia-induced BRB disruption respectively, which is associated with upregulation of its target VCAM-1 40,41 . In a rat model of contusion spinal cord injury model, miR-126 promoted angiogenesis and inhibited leukocyte extravasation and inflammation via targeting Spred-1, PI3KR2 and VCAM-1 42 .…”
Section: Dis-regulation and Beneficial Role Of Mir-126 In Vascular DImentioning
confidence: 97%
“…miR-126 also regulates BBB or BRB function. miR-126-3p mimic or miR-126 expressing plasmid attenuated hemorrhage-induced BBB or ischemia-induced BRB disruption respectively, which is associated with upregulation of its target VCAM-1 40,41 . In a rat model of contusion spinal cord injury model, miR-126 promoted angiogenesis and inhibited leukocyte extravasation and inflammation via targeting Spred-1, PI3KR2 and VCAM-1 42 .…”
Section: Dis-regulation and Beneficial Role Of Mir-126 In Vascular DImentioning
confidence: 97%
“…miR‐126, which is upregulated in chronic inactive lesions, might participate in this restoration. A recent study found that miR‐126‐3p reduced blood–brain barrier leakage following intracerebral hemorrhage via regulation of VCAM‐1 .…”
Section: There Is Significant and Reproducible Overlap Of Mirna Profimentioning
confidence: 99%
“…Considering this evidence, the accurate role and underlying mechanism of miR-340-5p in ICH attract our interest. Currently, the collagenase-induced model is widely used as a prevalent animal model to better mimic human ICH syndrome [21,22]. In the present study, the collagenase-induced ICH rat model was established to investigate the role of miR-340-5p in ICH-induced brain injury in vitro.…”
Section: Pdcd4 Was a Direct Target Gene Of Mir-340-5pmentioning
confidence: 99%